Properties of grey marl bricks with additions of rice husks - Zlateva Penka; Petkova-Slipets Rositsa; Yordanov Krastin (Magazine of Civil Engineering, 2023)
This article presents the results of experimental research on the impact of environmentally efficient materials developed on the basis of grey marl and sand with the addition of 3 % to 6 % of rice husk on the thermophysical characteristics: coefficient of thermal conductivity, specific heat capacity and thermal diffusivity. The thermal indicators are measured with a device based on the non-stationary method. The purpose of the research is to investigate the impact of a new type of a light natural organic additive material, the husk of rice grains, on the properties of the resulting composite. The task is to develop a new material which is both thermally efficient and eco-friendly. The results of the research show that the addition of rice husks reduces the coefficient of thermal conductivity by 42 %, of the thermal diffusivity by 38 %, and increases the specific heat capacity by 10 % compared to the reference sample.